Geodiversity, geoheritage and geotourism applied to the relief forms of the Microregion of Pau dos Ferros (RN, Brazil) (PerCursos, 2022)
The present study aimed to identify, spatialize and evaluate the geoheritage associated with mountainous geoforms in the Pau dos Ferros Microregion (MRPF), in the west of the state of Rio Grande do Norte (RN), which have geotourism potential. The methodological procedures were based on bibliographic research, observation of satellite images and field research. The results indicate five mountainous geomorphosites distributed in the municipalities of Portalegre (Torres de Pedra), Francisco Dantas (Serra da Madalena), Marcelino Vieira (Serra Panati) and Alexandria (Serra Barriguda and Serra de Santana) which were evaluated for the values of geodiversity, uses, aptitudes and protection. The results allow the proposition of a "mountainous geotourism circuit" in MRPF, a fact that would contribute to the valorization and geoconservation of the sites, in addition to fostering research on geodiversity, geoheritage and geotourism in the region.
Keywords: abiotic enviromental; natural heritage; geoforms; geomorphosites; tourism